2000
DOI: 10.1159/000025268
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Biocompatibility Analyses of Stents Coated with Diamond-Like Carbon by Flow Cytometry, Cell Growth Assays and Electron Microscopy

Abstract: Background: Coronary artery stents can induce platelet activation by shear forces and contact to the biomaterial. This activation is one important trigger for thrombosis. Coating of stents is a possible approach to prevent this side effect. The purpose of this study was to evaluate in vitro the biocompatibility of stents coated with diamond-like carbon (DLC). Materials and Methods: For in vitro testing, DLC-coated stents were compared with noncoated 316L stainless steel stents. For this purpose, cell culture a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The biological effect of a-C coatings on various metal or polymer substrates exhibited good biocompatibility and haemocompatibility in different lineages of cells. The proliferation rates of smooth muscle and endothelial cells cultured onto a-C-coated stents were neither affected nor reduced [23]. The surface roughness of a-C increased the cell adhesion and proliferation of human fibroblasts [35].…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…The biological effect of a-C coatings on various metal or polymer substrates exhibited good biocompatibility and haemocompatibility in different lineages of cells. The proliferation rates of smooth muscle and endothelial cells cultured onto a-C-coated stents were neither affected nor reduced [23]. The surface roughness of a-C increased the cell adhesion and proliferation of human fibroblasts [35].…”
Section: Resultsmentioning
confidence: 92%
“…A recent study showed that a-C coating on artificial hip joints reduced the wear debris [20]. Several in vitro studies have also demonstrated that a-C coatings improved the adhesion and growth of osteoblasts, reduced platelet attachment, and inhibited activation [22], [23].…”
Section: Introductionmentioning
confidence: 99%
“…The bioinertness of DLC has been confirmed in various studies. 7 12 For example, studies on the effects of DLC coatings on cells found no evidence of cytotoxicity, 12 and studies of the interactions of macrophages with DLC coatings have confirmed that DLC does not induce inflammatory reactions in cells. DLC has also shown excellent biocompatibility with blood monocytes; 9 this is crucial because monocytes control inflammatory reactions that can affect osteointegration of implants.…”
Section: Introductionmentioning
confidence: 99%
“…16) Chu et al shown better adhesion and high viability of ECs on a-C:H coated surface comparing with conventional stent materials of nickel titanium (Ni-Ti).…”
Section: Discussionmentioning
confidence: 99%
“…initially revealed that the a-C:H coatings improve the hemocompatibility of conventional stainless steel stents without suppression of compatibility for ECs in a comparative experiment using stainless steel stents and a-C:H coated stents in vitro. 16) Chu et al shown better adhesion and high viability of ECs on a-C:H coated surface comparing with conventional stent materials of nickel titanium (Ni-Ti). 17) The compatibility of various atomics incorporated in a-C:H films with endothelial cells has also been studied.…”
Section: Discussionmentioning
confidence: 99%